2019
DOI: 10.4054/mpidr-wp-2019-008
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic variation in child educational and socioeconomic attainment after parental death in Sweden

Abstract: In this study we use Swedish population register data to examine whether parental death differentially affects educational and occupational attainment according to the socioeconomic status of the parent who dies, and the socioeconomic status of the surviving parent and extended kin. That is, we examine whether parental death has an equalizing or exacerbating effect on offspring socioeconomic attainment, and also whether the socioeconomic status of the rest of the family plays a meaningful role in compensating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…Following these theories, parental loss can also be considered an early-life shock with potentially lasting impacts throughout the life course. Losing a parent in early life has been found to negatively affect a variety of later-life outcomes, including mortality (Rostila et al, 2012), educational attainment (Barclay and Hällsten, 2019;Berg et al, 2014;Gertler et al, 2004;Kailaheimo and Erola, 2016;Prix and Erola, 2017) and occupational outcomes (Barclay and Hällsten, 2019). For the particular case of Sweden, research has shown that losing a parent in early life or childhood can have lasting effects on a educational attainment (Barclay and Hällsten, 2019;Berg et al, 2014), occupational choices (Barclay and Hällsten, 2019), mental health (Berg et al, 2016;Persson and Rossin-Slater, 2018), self-injury behaviour (Rostila et al, 2016), and mortality (Rostila and Saarela, 2011).…”
Section: Theoretical Framework and Contextmentioning
confidence: 99%
See 4 more Smart Citations
“…Following these theories, parental loss can also be considered an early-life shock with potentially lasting impacts throughout the life course. Losing a parent in early life has been found to negatively affect a variety of later-life outcomes, including mortality (Rostila et al, 2012), educational attainment (Barclay and Hällsten, 2019;Berg et al, 2014;Gertler et al, 2004;Kailaheimo and Erola, 2016;Prix and Erola, 2017) and occupational outcomes (Barclay and Hällsten, 2019). For the particular case of Sweden, research has shown that losing a parent in early life or childhood can have lasting effects on a educational attainment (Barclay and Hällsten, 2019;Berg et al, 2014), occupational choices (Barclay and Hällsten, 2019), mental health (Berg et al, 2016;Persson and Rossin-Slater, 2018), self-injury behaviour (Rostila et al, 2016), and mortality (Rostila and Saarela, 2011).…”
Section: Theoretical Framework and Contextmentioning
confidence: 99%
“…Second, the death of a parent might reduce both the financial resources of the household and the household's time budget as the surviving parent bears the responsibility for both childcare and earnings. Thus, losing a parent can lead to reduced parental investment into children with negative consequences for education, labour market outcomes or health (Barclay and Hällsten, 2019;Gertler et al, 2004). Several studies have reported a negative impact of parental loss on educational attainment at different levels (Barclay and Hällsten, 2019;Berg et al, 2014;Gertler et al, 2004; Kailaheimo studies exploit self-reported data on stress (Brodsky, 2016;Huizink et al, 2003;Lindström et al, 2012;Taylor et al, 2010), others look at stressful events taking place in administrative data (Pesonen et al, 2011), while yet others analyze medical measures of cortisol, a stress-related hormone (Huizink et al, 2003).…”
Section: Theoretical Framework and Contextmentioning
confidence: 99%
See 3 more Smart Citations